Corporate Social Responsibility and Marketing: What Works and What Doesnât - Darsono, Licen Indahwati (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
Many companies choose to portray themselves as seeking the moral high ground and playing active role in society. This introduces an idea of corporate social responsibility. It has been argued that corporate social responsibility enhances corporate image (attitudinal dimension) and financial performance. However, some studies find negative impact of corporate social responsibility. Thus, it is debatable whether or not it pays organizations to play active role in society. This paper explores the importance of trust for making corporate social responsibility works. This paper also evaluates attitude and intention within relative attitudinal framework. The associations between trust, attitude and intention are also discussed and reviewed. Finally, a set of managerial implications is developed to address the problems peculiar to the corporate social responsibility and marketing.